Object Descriptor Combining Color and Detection - Yun Gao; Guo-wu Yuan; Hao Zhou; Xue-jie Zhang (Institute of Advanced Engineering and Science, 2013)
Object descriptor has become one of the key factors for a robust and accurate tracker. In this paper, we propose an object descriptor combining color information and motion detection. A tracked object can be described by its hue histogram excluding the background pixels around the tracked object for restraining the disturbing of complex background environments. During the tracking process, we model the object descriptor by Gaussian Mixture Model for adapting the appearance variation of the tracked object. Tracking experiments in the frame of particle filter show that our proposed object descriptor can effectively improve the robustness and accuracy of object tracking under the situations of complex environments and appearance variations. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2616